O nowych podejściach w badaniach sztuki greckiej na przykładzie wytwórczości rzeźbiarskiej - Bugaj, Ewa (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, Ośrodek Studiów Pradziejowych i Średniowiecznych w Poznaniu, 2018)
In the chapter concerning the new approaches in the study of Greek sculptural production at first Ewa Bugaj considers the problem of putting the ancient artefacts with the modern works of art on the same level and the need for the new conceptualisation of them. In the next step she outlines historiography of the Greek sculpture with the particular reference to the study on their stylistic development. Further on the author presents selected, new approaches in the study on Greek sculpture, the ones which are breaking the long tradition of research on them, rooted in the Enlightenment and Hegelian thought and historicism. She focusses on the results of these research which shift the interpretative emphasis from the relation between the image/ sculpture and its model to that of the image and its viewer.
The New Approaches in Research on Greek Art on the Example of Sculptural Production
Keywords: starożytna rzeźba grecka; Ancient Greek Sculpture; starożytne sztuka grecka; Ancient Greek Art; archeologia klasyczna; classical archaeology; metody i teorie archeologiczne; archaeological methods and theory; archeologia i sztuka starożytnej Grecji; Greek Archaeology and Art; historiografia rzeźby greckiej; historiography of Greek sculpture; styl klasyczny w rzeźbie greckiej; classical style in Greek sculpture; funkcje rzeźby greckiej; function of Greek sculpture